Selection Of Lactic Acid Bacteria as Starter Culture for Cocoa Fermentation (Theobroma Cacao L.) - Hanni Tsaaqifah; Anja Meryandini; Fahrurrozi Fahrurrozi (Postgraduate, University of Mataram, 2023)
This research aims to select the potential lactic acid bacteria (LAB) for starter culture for cocoa beans fermentation. The bio-control activity against mycotoxigenic fungi were also evaluated. The indigenous LAB was analized from Sukabumi cocoa beans fermentation by spontaneous method for four days (96 hours). The preliminary screening of LAB were observed by clear zone forming, morphology characterization and catalase activity. The LAB were screened for their ability to resist acidity, ethanol, and heat, and their ability to produce high acid and antifungal. The antifungal capability was antagonistic assays to Aspergillus ochraceus IPBCC 88.033 on Potato Dextrose Agar (PDA) medium. Â The result showed that the selected acid bacteria isolate, H 2.34, were antifungal-producing strains, and resist acidity, ethanol and heat, which was suitable property for starter culture and biopreservation agent. The study demonstrated the selection of local Indonesian LAB from Sukabumi fermented cocoa bean to observe the potential of isolate as a starter culture and biopreservation agent